Rape Myth Acceptance of Police Officers in Portugal - Fávero, Marisalva (Journal of interpersonal violence, 2022)
This study intended to examine rape myth acceptance (RMA) among police officers and its relationship with sociodemographic data, length of service, specific training in the field, and professional experience with victims of rape. To this end, we applied the Sexual Violence Beliefs Scale (ECVS) and controlled for sociodemographic data, as well as professional experience and specific training in the field, through a self-report questionnaire. The sample was composed of 400 police officers from a city in the north of Portugal, aged between 29 and 54 years, and most were men (94.3%). We found that tolerance to overall sexual violence exhibits positive correlations with age and length of service, as well as negative correlations with education levels. Differences were also found regarding gender, with men exhibiting greater tolerance/acceptance of overall sexual violence. It was also found that officers who exhibit higher tolerance/acceptance for sexual violence, overall, are those who do not consider it relevant to receive specific training in the field of sexual violence to perform their duties, who report not having any professional experience with cases of sexual violence and also do not consider it necessary to have specific abilities for these types of cases. Implications for decision-making in legal proceedings are discussed, stressing the need for specific specialization in intervention with victims of sexual assault, with a strong practical component.